Computer Aided Instruction (CAI) for biology curriculum (learner centered approach) - Phan, Kar Yu (2020)
This project is an multimedia design project for academic purpose. A multimedia courseware will be developed to deliver the information of biology to the students. The multimedia courseware is the methodology of combining the method of teaching and the form of game in order to attract the students and increase their interests in study. The multimedia courseware will be focus on the topic of endangered ecosystem in the form 4 biology and the target audience is form 4 students. The objectives of this project is to design a highly interactive multimedia courseware in order to increase the engagement for user to learn the biology. The learning-centered approach had been used to develop the multimedia courseware so that it can place the learner at the center of the learning. Moreover, it also can help the user to solve the problems and relect on what they are learning. The multimedia courseware consists of 5 modules which are learning module, experiment note module, quiz module, past year paper module and game based learning module. Each modules has its functionalities and specialization to provide the information of the endangered ecosystem for the user. The multimedia courseware also consists of multimedia elements such as texts, graphic, audio, video and animation to increase the user experiences. Hence, it can motivate the students to learn the biology when compared to the traditional way of study. The theory and main points of the endangered ecosystem will be provided in the learning module and the knowledge of experiment will be provided in the experiment note module. User also can increase their understanding by answering the questions in the quiz module and the questions of paper 1, paper 2 and paper 3 in the past year paper module. The creative game based learning module can allows user to interact and engage in the game. As a result, user can explore the knowledge of biology and they can understand the biological concept from these 5 module in the multimedia courseware. The methodology for this multimedia project is ADDIE model. It consists of 5 phases which are analysis, design, development, implementation and evaluation phases. The unrealistic requirements, cause of problems and the possible solutions will be identified during the analysis phase. Furthermore, the storyboards and the survey questionnaire will be done in the design phase. Next, the system will be developed in the development phase. After that, it will be delivered to the target audience and the feedbacks will be collected in the implementation phase. Lastly, the system will be tested and improved in the evaluation phase. Each of the phase will be gone through to produce the multimedia courseware successfully.